Potential of peptides and phytochemicals in attenuating different phases of islet amyloid polypeptide fibrillation for type 2 diabetes management - Raliat O. Abioye; Chibuike C. Udenigwe (Food Science and Human Wellness)
Islet amyloid polypeptide (IAPP), or amylin, has been identified as a key factor in the development of type 2 diabetes (T2D). IAPP aggregates, which form amyloid fibrils, contribute to cytotoxicity of the pancreatic β-cells, resulting in loss of function and subsequent reduction in insulin production. As a result, surviving β-cells overcompensate for this reduction of insulin production, further contributing to the loss of function because of increased stress, thus leading to insulin resistance. Endogenously, IAPP monomers function in a variety of roles; however, aggregation renders them non-functional. The use of naturally occurring compounds, including peptides and phytochemicals, has been explored as a way to mitigate or inhibit IAPP fibril formation. This review discusses the structure, endogenous roles and mechanism of IAPP fibril formation, recent advances on inhibitors of IAPP fibril formation, and new insights on the future development and application of food-derived inhibitors towards T2D management.